Humanity’s environmental problems can only be fixed by changing the system. The coronavirus offers a chance. - Graeme Maxton (The White Horse Press, 2020)
Societies need to introduce much more radical emissions reductions targets than those agreed in Paris if they are to successfully slow the pace of change. Covid-19 makes this possible. By forcing aviation and other transportation businesses to downsize emissions have started to fall. By paying people to stay at home governments have shown that they can support them during a transition. Societies should grasp this unique chance for radical social and economic reform.